Path Relationship of Time Management and Academic Achievement of Students in Distance Learning Institutions: Saghir Ahmad ,Ayesha Batool ,Abid Hussain Ch (PJDOL, 2023)
The primary achievement of distance and regular students is managing time effectively. Mismanagement disturbs the academic achievements of learners. Time administration plays a significant role in improving learners’ performance and accomplishments. It is a skill to manage timeand every learner must familiar and command on this skill for the sake of better results.